Blended Learning dalam Pembelajaran Bahasa Arab di Era Society 5.0: Problematika dan Solusinya - Jamil, Husnaini; Agung, Nur (IAIN Bone, 2021)
The process of learning Arabic in Indonesia at this time has experienced a shift in orientation from understanding the structure of the language to mastering Arabic as daily communication. This new orientation requires a new learning model that is comprehensive and covers all aspects of education. The Blended Learning model is here to help achieve this orientation by combining face-to-face learning, distance learning (online), and independent learning (offline) in one opportunity by making technology the main tool that supports its successful implementation. It is hoped that with this learning model, the competence of students can increase and the problems of learning Arabic that have been developing so far can increase the marginalized so as to make Arabic one of the foreign languages that are in demand by the Indonesian people.